Short-Term Treatment with Rosuvastatin Reduces Systemic Inflammation in Stable COPD Patients - Nierengarten, Mary Beth (MD Conference Express, 2014)
This article discusses results of the Effect of Rosuvastatin Treatment in Stable COPD study [RODEO; NCT00929734; Neukamm A et al. Am J Respir Crit Care Med 2014], a randomized, double-blind clinical trial conducted to test the hypothesis that the use of statin therapy in patients with stable chronic obstructive pulmonary disease (COPD) would be associated with improved endothelial and pulmonary function and reduced systemic inflammation.